Experimental study on thermal runaway and its propagation in the large format lithium ion battery module with two electrical connection modes. (15th August 2020) - Huang, Zonghou; Zhao, Chunpeng; Li, Huang; Peng, Wen; Zhang, Zheng; Wang, Qingsong
Abstract: This paper experimentally investigated the thermal runaway (TR) characteristics of lithium ion batteries (LIBs) with different state of charges (SOC) and its propagation in the large format module with different electrical connection. Some critical parameters of LIBs with different SOCs such as temperature, voltage, mass loss, heat release rate, released gas during TR were analyzed. The results indicated that the TR severity of LIB with 100% is much higher than that of LIB with 50% SOC. The generations of combustible and toxic gases for LIB with 100% SOC are much higher than those of 50% SOC. Based on the experiment results, the modules consisting of four LIBs with 100%SOC were built to investigate the effect of electrical connection on TR propagation characteristics. It was found TR propagates faster in parallel module than in series and unconnected modules, and TR spreads faster in series modules than in unconnected module. Moreover, the average maximum temperature of the module in parallel is about 30 °C higher than that of module in series. A significant time delay of TR propagation time between the last two LIBs in parallel module was observed. Finally, the heat transfer between LIBs was calculated. Highlights: The TR propagation in large format lithium-ion battery modules with two electrical connection modes are investigated. The effect of electrical connection on TR propagation are discussed from the perspective of heat path and electric path. The critical characteristic of lithium-ion batteries with different SOCs during TR were analyzed.